A multicriteria comparison of utilizing sugar cane bagasse for methanol to gasoline and butanol production. (December 2016) - Michailos, Stavros; Parker, David; Webb, Colin
Abstract: The present study makes a consistent and comparative assessment of the overall exergy, financial and environmental efficiencies of two biomass-to-fuels (utilised in internal combustion engines with spark ignition) conversion options and based on this result, gives a recommendation as to which of the options assessed is most desirable. These options are methanol to gasoline (MTG) and biochemical butanol, while as feedstock the solid residue of sugar cane, bagasse, was considered. For the work presented in this study, a base case scenario has first been developed for each pathway by employing either Aspen Plus or SuperPro Designer (as simulators) to perform mass and energy balance calculations while Matlab software has been used for modelling the reaction kinetics of each process. Based on the simulations, thermodynamic (exergy analysis), economic (financial and risk analysis) and environmental (CO2 emissions) evaluations were carried out. Afterwards, sensitivity analyses have been performed in order to define the key parameters of each conversion route. Exergy and economic analysis favour the gasoline production while butanol produces less CO2 emissions. The study concludes with multicriteria decision analysis (MCDA) where each process is issued a score according to the investigated criteria. This makes it possible for the investigated procedures to be compared on the same basis. According to this analysis, the production of gasoline achieves a higher overall score than butanol production, i.e. 97% and 90% respectively. Highlights: Synthetic fuel production from sugar cane residue has been successfully simulated. Application of multicriteria decision analysis to biorefinery waste utilization. Gasoline production from bagasse is more favourable than butanol production.